Quality and Potency of Government-subsidized Antibiotics in Hospitals Across Jakarta, Indonesia - Khairani, Sondang; Ramadaniati, Hesty Utami; Sarnianto, Prih; Kristin, Erna; Anggriani, Yusi (Sciences of Pharmacy, 2024)
Several pharmaceutical companies have long complained that the price of medicines that win the e-catalogue tender is too low, in some cases even below the cost of production. However, it should not be a concern that only pharmaceutical products with regulation of Indonesian food and drug (BPOM) distribution licenses are eligible for the price tender, as they are of good quality. This study aims to determine the quality and potency of three antibiotic drugs based on their highest utilization (DU 90%) in pneumonia patients at two hospitals, A (ceftriaxone, azithromycin tablet) and B (ceftriaxone, levofloxacin infusion) compared to brand name. The quality of the samples was evaluated following the Indonesian Pharmacopoeia 6th Edition (FI-VI). Antibiotic potency was assessed using the Plate-Cylinder Method with K. pneumonia from human and S. pneumonia ATCC 10015 as the test bacteria evaluated following CLSI. All samples meet the criteria of FI-VI antibiotic content, weight uniformity, dissolution. Antibiotic potency all samples test S.pneumonia and K.pneumonia were sensitive but ceftriaxone test with K.pneumonia was resistance. All antibiotic tablets and injections studied met the requirements of the Indonesian Pharmacopoeia Edition 6 for active medicinal ingredient content, dosage weight uniformity, and dissolution. All drugs from hospitals (INN) have lower antibiotic potency than branded drugs. This highlight the importance of conducting microbiological testing on antibiotic preparations.